Polar research infrastructure network: the Ukrainian input - Biebow, Nicole; Willmott Puig, Veronica; Dykyi, Evgen; Fedchuk, Andrii; Zherebchuk, Sofia; Kryvytska, Yuliya; Marushevska, Olena; Torgonenko, Anna (Ukrainian Antarctic Journal, 2024)
The polar regions play a crucial role in the Earth’s system. They are essential for our climate and are sentinels of climate change and human expansion. The polar research community needs access to world-class research infrastructure operating on-site to understand and predict essential processes in the polar regions and provide evidence-based information. To address that, a consortium of the European Union and international polar research operators is joining their efforts in the Polar Research Infrastructure Network (POLARIN) project. POLARIN is an international network of polar research infrastructure and services, aiming to address the polar regions’ scientific challenges. The network includes various complementary and interdisciplinary top-level research infrastructure: Arctic and Antarctic research stations, ice-capable research vessels, observatories, data bases, and ice core and sediment repositories. This article aims to highlight Ukraine’s role in the global effort to study and understand the polar regions, focusing on its participation in POLARIN project and the significance of its potential contributions. It is argued that Ukraine has played a role in shaping policies for creating an international network of polar infrastructure issues by sharing research facilities, contributing data and insights to global discussions on environmental conservation, climate change mitigation, and sustainable development in the polar regions.